Answer :

We have been given that,

a * b = a × b + (a × a + b × b) …(i)


Apply the same formula in the questions that follows:


(i) We have (-3) * (-5)


Put a = -3 and b = -5 in equation (i), we get


(-3) * (-5) = [ (-3) × (-5) ]+ (-3 × -3 + -5 × -5)


(-3) * (-5) = 15 + (9 + 25)


(-3) * (-5) = 15 + 9 + 25


(-3) * (-5) = 49


Thus, the answer is 49.


(ii). We have (-6) * 2.


Put a = -6 and b = 2 in equation (i), we get


(-6) * 2 = [ (-6) × 2 ] + (-6 × -6 + 2 × 2)


(-6) * 2 = -12 + (36 + 4)


(-6) * 2 = -12 + 40


(-6) * 2 = 28


Thus, the answer is 28.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
RELATED QUESTIONS :

Water level in a NCERT - Exemplar Mathematics

<span lang="EN-USNCERT Mathematics

Write a pair of iNCERT - Exemplar Mathematics

If * is an operatNCERT - Exemplar Mathematics

State whether theNCERT - Exemplar Mathematics

<span lang="EN-USNCERT Mathematics

Evaluate the follNCERT - Exemplar Mathematics

Write a positive NCERT - Exemplar Mathematics

Write a positive NCERT - Exemplar Mathematics